TransNIEMO: Economic Impact Analysis Using a Model of Consistent Interregional Economic and Network Equilibria - JoongKoo Cho; Peter Gordon; James E. Moore II; Qisheng Pan; JiYoung Park; Harry W. Richardson (Center for Economic Studies and ifo Institute (CESifo), 2014)
We describe a model that integrates a multi-regional input-output model of the U.S. (50 states and the District of Columbia) with the national highway network. Interstate commodity shipments are placed on a congestible highway network. Simulations of major choke-point disruptions redirect traffic which increases the costs of some shipments. Increased costs show up in higher prices which help to determine a new input-output equilibrium. We find economic and network equilibria that are consistent. The simulations show only moderate economic impacts. We ascribe this to the resilience of highway network. The model provides state-level detail on who bears the costs of the disruptions.
Keywords: R11; R12; R13; R15; R40; R41; R49; 330; multi-regional input-output model; highway network; interstate commodity shipments; highway infrastructure failure